2016
DOI: 10.1016/j.jpainsymman.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The Social Convoy for Family Caregivers Over the Course of Hospice

Abstract: Context Family caregivers provide a central role in the care of those in hospice care. Little is known about the social support networks for those providing this day to day care without training. Objectives The purpose of this study was to explore changes in family and friend social networks among hospice caregivers over the course of the hospice stay. Methods Data on social support networks was collected as part of a multi-site randomized controlled trial and analyzed using structural equation modeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…It has been found that hospice social workers do not use standardized assessment tools to determine families’ long-term financial wellbeing. (Parker Oliver, Wittenberg-Lyles, Washington, & Sehrawat, 2009; Washington et al, 2016). While there are existing assessment instruments that address families’ financial wellbeing (Cagle et al, 2017b), they often focus solely on the adequacy of existing resources to maintain safe and appropriate patient care.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that hospice social workers do not use standardized assessment tools to determine families’ long-term financial wellbeing. (Parker Oliver, Wittenberg-Lyles, Washington, & Sehrawat, 2009; Washington et al, 2016). While there are existing assessment instruments that address families’ financial wellbeing (Cagle et al, 2017b), they often focus solely on the adequacy of existing resources to maintain safe and appropriate patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, interventions have been developed to test programs seeking to improve caregivers' social support (e.g., Dam, de Vugt, Klinkenberg, Verhey, & van Boxtel, 2016). Other researchers have used a convoy approach to address specific caregiving circumstances, such as end‐of‐life care (Albright et al, 2016) or caregiving in blended families (Sherman et al, 2013). Albright et al (2016) found that the size of family convoys decreases for caregivers during hospice, suggesting the need for intervention to foster better convoy support during this time.…”
Section: Opportunities For Future Innovationmentioning
confidence: 99%
“…Other researchers have used a convoy approach to address specific caregiving circumstances, such as end‐of‐life care (Albright et al, 2016) or caregiving in blended families (Sherman et al, 2013). Albright et al (2016) found that the size of family convoys decreases for caregivers during hospice, suggesting the need for intervention to foster better convoy support during this time. Sherman et al (2013) demonstrated both positive and negative attributes in their research on dementia caregiving in late‐life remarriages in which negativity and tension were experienced between spousal caregivers and stepchildren in particular.…”
Section: Opportunities For Future Innovationmentioning
confidence: 99%
“…Our finding with regard to decreasing social QoL is consistent with a recent study that evaluated social networks for hospice caregivers. Albright et al 8 found that caregivers’ social networks decreased significantly during their hospice enrollment, underscoring a possible connection between the size of one’s social support system (i.e., their social network) and their social quality of life.…”
Section: Discussionmentioning
confidence: 99%